Moderasi dalam Rekrutmen Politik Partai Keadilan Sejahtera (Studi Hukum tentang Inklusivitas Partai Politik) (RechtJiva, 2024)
The Prosperous Justice Party (Partai Keadilan Sejahtera or PKS), a political party with an ideology based on Islam as stated in its Articles of Association, initially aimed to be a da'wah party with the goal of creating a just and prosperous society based on Islamic principles. However, in recent years, there has been a shift in policies indicating steps towards moderation, especially concerning more inclusive political recruitment. These moderation steps include changes in the party's goals and a more open approach towards members and candidates from diverse backgrounds, as well as equal treatment of gender differences. Using legislative and conceptual approaches, this normative juridical research analyzes the legal considerations behind PKS's adoption of inclusive moderation policies in political recruitment and how the concept of inclusivity in such moderation is implemented by PKS. This study concludes that there are relevant legal considerations as the basis for PKS in determining inclusive and moderate policies, as well as their relevance to Law No. 2 of 2008 on Political Parties and other related laws. This research also provides a legal perspective on the political and ideological dynamics that influence PKS's political recruitment policies.